Governing Knowledge
XVI, 279 p.
Keywords: In this book, an international group of leading higher education researchers draw on a wealth of social theory and comparative, empirical research to analyse current developments and their implications. Different contributions focus on different levels of higher education, the system, the institution and the academic practitioner, in different national and international contexts. However, strong common themes bind these contributions together. They include not only the significance of massification, globalisation, neo-liberalism and managerialism for the governance of higher education, its knowledge and values, but also the complexities of change processes, the importance of context and history and the strength of the stabilities that remain. The inspiration for this work comes from the career and personal influence of an individual scholar, Maurice Kogan. A central feature of his work has been empirically grounded analysis of interconnections between knowledge, values, authority and power and how these are reflected in institutional structures and individual practices. As a historian as well as a political scientist, he has always insisted on locating contemporary developments in a longer term perspective. This volume is for researchers in higher education studies, students in postgraduate courses in higher education policy and management, higher education policy makers in national and international organisations, higher education institutional leaders, senior academics, managers and administrators. Professor Teboho Moja, New York University, USA: "It will be an invaluable resource inter alia for higher education students, scholars, and institutional leadership." "The book could provide a major contribution to the field of higher education because of the different perspective different authors present and an array of issues as well as frameworks to discuss them." "This book is bound for the desktops instead of the bookshelves of administrators, researchers, and graduate students. It is likely to be used time and again as readers explore new ways to transform education systems or institutions, meet their needs for program improvement, policy development, and general research. I expect that most readers will weave through the chapters (...) on an as-needed basis, until they have engaged all its excellent content.".